BRAZILIANSUPREMECOURTAND THE ELECTIONS PROPAGANDA - Napolitano, Carlo José [UNESP] (Instituto Rede de Pesquisa Empirica em Direito (REED), 2019)
The present essay is a research report that considers that since the 90’s the Brazilian Supreme Court began to play a role of centrality in Brazil’s political decisions, in addition to performing its essential function of guardian of the Constitution. Some of the STF political decisions hypothetically impact the media and the activities of the media, influencing the exercise of freedom of speech, democracy and citizenship, as well as established criteria that guide the formulation and implementation of public policies on communication. In this context, the proposal aims to investigate decisions made by the Supreme Court in the period 1988-2016 and that relate to the proposed theme, in order to investigate if there is a modus operandi of the Brazilian Supreme Court in the judgments about the public policies of communication related to the freedom of speech. The present study aims to show and discuss the findings of the research related to the topic of the elections propaganda, concluding that it is not possible to indicate a modus operandi in the Brazilian Supreme Court judgments about freedom of speech when related to this public communication policy.
SUPREMO TRIBUNAL FEDERAL E AS PROPAGANDAS ELEITORAIS
Keywords: Brazilian Supreme Court; elections propaganda; public policies of communication